WORK STRESS AND BURNOUT : SISTEMATIC LITERATUR REVIEW (SLR) DAN ANALISA BIBLIOMETRIK - Mubarok, Dimas Hamdan; Sopiah, Sopiah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This Systematic Literature Review (SLR) employs the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) methodology and VosViewer bibliometric analysis to investigate work stress and burnout. Data were extracted from Sciendirect, covering the period from 2021 to 2023. Initially identifying 118 journals, stringent inclusion and exclusion criteria were applied, resulting in a focused set of 31 journals for comprehensive review. The review reveals a prevalent experience of work stress and burnout among employees. This underscores the urgency of implementing measures to minimize these issues, as their persistence could lead to detrimental consequences for companies. Consequently, the study emphasizes the critical importance of proactive strategies to mitigate work-related stress and burnout, not only for the well-being of employees but also to safeguard overall organizational health and performance. Recognizing the significance of addressing these challenges, organizations are urged to prioritize interventions and initiatives that foster a healthier work environment and contribute to sustained employee satisfaction and productivity.